Wpływ nawożenia organicznego i ściółkowania na wzrost modrzewia europejskiego (Larix decidua L.) oraz aktywność biologiczną gleb - Klimek, Andrzej; Hilszczańska, Dorota; Rolbiecki, Roman; Rolbiecki, Stanisław (Leśne Prace Badawcze, 2011)
The purpose of the study was to determine the influence of organic fertilization and mulching with ectohumus on the growth of two-year old European larch seedlings ( Larix decidua L.) and biological properties of soils in forest nursery under conditions of micro-sprinkler irrigation. The experiments were carried out on the rusty soil in forest nursery Białe Błota (Forest District Bydgoszcz). The use of organic fertilization with treated sewage sludge with the bark or sawdust additives, did not differ significantly the growth parameters of seedlings. Mulching with the cap-humus from the fresh coniferous forest significantly increased the height and the fresh mass of above-ground parts of two-year old European larch seedlings. The use of sewage sludge with the bark or sawdust additives did not effect negatively on the state of mycorrhizal structure in the juvenile phase of seedlings. The treatment of mulching influenced positively on the biological condition of nursery soils – the dimension of saprophage oribatid mites was characterized by the manifold increase.